2003
DOI: 10.1021/nl0343710
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Field Enhancements from Metal Nanoparticle Arrays

Abstract: Theoretical and semiempirical studies of two-dimensional (2D) metal nanoparticle arrays under periodic boundary conditions yield quantitative estimates of their electromagnetic (EM) field factors, revealing a critical relationship between particle size and interparticle spacing. A new theory based on the RLC circuit analogy has been developed to produce analytical values for EM field enhancements within the arrays. Numerical and analytical calculations suggest that the average EM enhancements for Raman scatter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
321
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 384 publications
(339 citation statements)
references
References 31 publications
15
321
3
Order By: Relevance
“…Tailoring and controlling optical near-fields in plasmonic nanostructures facilitate the enhancement of numerous linear and nonlinear optical effects [45,50,51,52,53]. Applications are diverse and include surface enhanced Raman scattering [1,2], second [3,4] and third [5,6] harmonic generation, two-photon photoluminescence [59,60], continuum generation [61] or localized multiphoton photoemission [7,8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tailoring and controlling optical near-fields in plasmonic nanostructures facilitate the enhancement of numerous linear and nonlinear optical effects [45,50,51,52,53]. Applications are diverse and include surface enhanced Raman scattering [1,2], second [3,4] and third [5,6] harmonic generation, two-photon photoluminescence [59,60], continuum generation [61] or localized multiphoton photoemission [7,8].…”
Section: Methodsmentioning
confidence: 99%
“…The optimization of the evaporation conditions improved the surface roughness (measured by the root-mean-squared (RMS) value of the surface height) and enabled the fabrication of high quality nanoantennas. Plasmonic nanostructures offer unique possibilities for enhancing linear and nonlinear optical processes [45,50,51,52,53,6]. Recently, Kim et al [24] reported nanostructure-enhanced high harmonic generation (HHG).…”
Section: Home-built Vacuum Setup For Euv Light Generation and Spectramentioning
confidence: 99%
“…16(a)). 51,52 These local SERS enhancements can be many orders of magnitude greater than the surface-averaged enhancements, making self-assembly an appealing method to develop well-defined 'hot spots' for ultrasensitive SERS spectroscopy. On the other hand, restricted access to these highly active sites limits the usefulness of the close-packed 2D arrays for analyte detection.…”
Section: Optical Properties Of Gold Nanoparticle Arraysmentioning
confidence: 99%
“…8,9,10 Theoretical studies of metal nanoparticle arrays have indicated that both local and surface-averaged field enhancements can be optimized at a given frequency as a function of size and interparticle spacing. 11,12,13, 14 We have determined that 2D arrays of closely spaced cylindrical nanoparticles (i.e. nanorods) provide a nearly ideal geometry for generating local field factors with maximum intensity.…”
Section: Introductionmentioning
confidence: 99%